2018
DOI: 10.1002/chem.201705983
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐Substituted Hydrocarbon Diastereomer Combinations Reveal Stapled Peptides with High Structural Fidelity

Abstract: Modified peptides, such as stapled peptides, which replicate the structure of α-helical protein segments, represent a potential therapeutic advance. However, the 3D solution structure of these stapled peptides is rarely explored beyond the acquisition of circular dichroism (CD) data to quantify bulk peptide helicity; the detailed backbone structure, which underlies this, is typically undefined. Diastereomeric stapled peptides based on helical sections of three proteins (αSyn, Cks1 and CK1α) were generated; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…As shown in Figure C, peptide 1R with longer retention time on HPLC showed more higher helical contents than peptide 1S , which is in agreement with our previous work, demonstrating that the CIH concept could be translated into an all‐hydrocarbon tethered peptide. Notably, the α‐methyl group in the olefinic amino acid is not necessary for constructing CIH helical peptides . Furthermore, comparing with the thioether tethered CIH peptide previously reported by our group, the all hydrocarbon CIH peptide 1R showed higher helical content than its thiolether tethered counterpart 2R , shown in Figure 3C …”
Section: Results and Disscussionmentioning
confidence: 67%
“…As shown in Figure C, peptide 1R with longer retention time on HPLC showed more higher helical contents than peptide 1S , which is in agreement with our previous work, demonstrating that the CIH concept could be translated into an all‐hydrocarbon tethered peptide. Notably, the α‐methyl group in the olefinic amino acid is not necessary for constructing CIH helical peptides . Furthermore, comparing with the thioether tethered CIH peptide previously reported by our group, the all hydrocarbon CIH peptide 1R showed higher helical content than its thiolether tethered counterpart 2R , shown in Figure 3C …”
Section: Results and Disscussionmentioning
confidence: 67%
“…Among all obtained stapled peptides, mS5-mS5 mediated Cks1 and CK1α peptides and mS5-mR5 αSyn showed the highest helicity based on CD analysis, indicating that the helixstabilizing effect in this mS5/mR5 stapling was sequencedependent. 202 This result was subtly different from the application of regular α,α-disubstituted amino acids, in which S5-S5 paired anchoring residues were optimal in most cases.…”
Section: Alkenyl-substituted Alanine and Its Derivatives For Rcm Stap...mentioning
confidence: 89%
“…The enantiomer of the mS5 nonnatural amino acid, termed mR5, was next prepared by Hulme and co-workers. 202 All possible diastereomers of paired anchoring residues mS5-mS5, mR5-mR5, mR5-mS5, and mS5-mR5 were incorporated at the appropriate i, i+4 positions of three peptide candidates, including a 14-mer from the protein alpha-synuclein (αSyn), a 12-mer from the accessory protein cyclin-dependent kinase regulatory subunit 1 (Cks1), and a 10-mer from casein kinase 1 alpha (CK1α), to yield the desired stapled peptides. 202 The on-resin RCM reaction proceeded efficiently under the more helix-promoting solvent TFE in DCM but not in the commonly used DCE solvent.…”
Section: Alkenyl-substituted Alanine and Its Derivatives For Rcm Stap...mentioning
confidence: 99%
“…Indeed, McWhinnie et al have reported three hydrocarbon-stapled peptide series which reproduce the secondary structure of the native protein they were extracted from (αSyn, CKS1 and CK1α) with high fidelity, whereas the unstapled natural sequences displayed almost no secondary structure content ( Figure 3A). [64] Similarly, Wang et al have isolated a minimum helical motif from the coiled-coil region identified in the crystal structure of the respiratory syncytial virus fusion (RSV-F) protein, [65] and then enhanced the helicity of this initial peptide sequence using computational mutagenesis and all-hydrocarbon peptide stapling, achieving a corresponding 2-fold improvement in binding affinity.…”
Section: Excision Of a Helical Fragment From A Proteinprotein Intermentioning
confidence: 99%